MEASUREMENT OF EMPLOYEE MOTIVATION USING MULTIDIMENSIONAL WORK MOTIVATION SCALE AND MOTIVATION AT WORK SCALE AT PT. BANK RAKYAT INDONESIA (PERSERO) TBK. SISINGAMANGARAJA BRANCH MEDAN - Hestianti, Maya (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2025)
From the initial research that researchers did, related tomotivation in general showed that measurement of employeemotivation was important to be done in order to assistmanagement in making decisions regarding human resourcesand finding ways to achieve maximum performance forunmotivated employees. Motivation carried out by PT. BRI(Persero) is still less than optimal because there are still manyemployees whose work is assisted by other people such asschoolgirls who are apprenticed. This reflects the motivation inPT. BRI (Persero) has not improved the performance of itsemployees themselves. The purpose of this study was todetermine the effect of multidimensional work motivation scaleand motivation at work scale on the level of motivation ofemployees at PT. People's BankIndonesia(Persero) Tbk.Sisingamangaraja Medan Branch. The number of samples inthis study was 86 people using saturated sample techniques.The analysis technique used is multiple linear regression. Theresults show that multidimensional work motivation scale has asignificant effect on employee motivation. While the variablemotivation at work scale has no significant effect on employeemotivation. Multidimensional variables work motivation scale andmotivation at work scale simultaneously have a significant effecton employee motivation